QUALITY CHARACTERISTICS OF PALM SUGAR (CASE STUDY IN UD SOBAR BULUMARIO VILLAGE AND SIMANINGGIR VILLAGE SIPIROK DISTRICT TAPANULI SELATAN DISTRICT) - Bustanul Arifin Dalimunthe; Santosa; Azrifirwan (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This research aims to determine the quality of palm sugar produced by UD Sobar. The samples were taken from the two factories owned by UD Sobar located in Bulumario Village and Simaninggir Village. The parameter that is used to determine the quality of the palm sugar produced by UD Sobar is SNI (SII 0265-85). The parameters in SNI (SII 0268-65) are total sugar (reducing sugar and sucrose), reducing sugar, sucrose, water, ash, insoluble parts, pigment, starch, dangerous metal form and content. Additional testing that has been done is a pH test and color scale test. The result of the test on palm sugar sample produced in Bulumario Village, the ash content is not up to SNI standard (SII 0268-85) which is 2.73% (maximum SNI requirement of 2%). Whilst in the sample from Simaninggir Village, the parameters that are not suitable are total sugar 79,